(untitled) (BSAA arte, 2025)
This study examines the award distribution boards of 1778 and 1782 at the School of the Three Noble Arts of Seville, focusing on the participants and the works presented. It highlights the influence of classical sculpture, promoted by the Royal Academic of San Fernando as an educational model, although Francisco de Bruna chose to uphold the local Baroque tradition in organizing the competitions. Finally, the study reflects on the limited historiographical recognition that eighteenth-century artistic production has received, as evidenced by the works analysed here, emphasizing the need for its reassessment and preservation.